Patient-Centered Reduction or Discontinuation of Long-term Opioid Analgesics - Yoan, Yoan; Jessica, Jessica (International Medical Journal Corp. Ltd, 2024)
Background: The literature illustrates a growing consensus on the need for patient-centered approaches to opioid tapering, emphasizing effective communication, shared decision-making, and the importance of support systems. However, significant gaps in evidence and methodological rigor persist, necessitating ongoing research and the development of comprehensive strategies for safely managing opioid discontinuation in chronic pain patients. Literature Review: The literature surrounding the reduction or discontinuation of long-term opioid analgesics reveals a multifaceted landscape that underscores the necessity for patient-centered approaches in managing chronic non-cancer pain (CNCP). A significant concern raised by (Eccleston et al., 1970) is the alarming rise in opioid prescriptions, which correlates with increasing overdose rates, prompting a reevaluation of prescribing practices. Conclusion: In conclusion, the literature emphasizes a growing consensus on the importance of patient-centered strategies for opioid tapering, encompassing effective communication, shared decision-making, and robust support systems. However, significant gaps in evidence and methodological rigor remain, underscoring the need for further research and the development of comprehensive protocols to ensure safe and effective opioid discontinuation for patients with chronic pain.